A partial enlightenment: what modern literature and Buddhism can teach us about living well without perfection - Alpert, Avram (Columbia University Press, 2021)
Acknowledgments -- Introduction -- 1. Enlightenment -- 2. Reincarnation -- 3. Liberation -- 4. Authenticity -- Coda -- Notes --Bibliography -- Index.